Blood metabolites, protein regulatory networks and their roles in pan-cancer: a mendelian randomisation study - Shenglong Xia; Zhengyang Xu; Cheng Cheng; Rui An; Wenci Chen; Daopo Lin; Yuzhen Gao; Liangjing Wang; Xinyou Xie; Jun Zhang (Discover Oncology)
Abstract Background Metabolic dysregulation was closely associated with cancers. However, there is a lack of studies to explore the relationship between blood metabolites, related proteins, and different types of cancer. Methods Two-sample Mendelian randomization (MR) analysis was used to assess the causal effects of genetically determined metabolites and metabolite ratios on solid cancers. we analyzed 1400 metabolites/metabolite ratios as exposures and 16 cancers from UK Biobank/FinnGen as outcomes. Protein-metabolite interactions were mapped via MR and visualized with Cytoscape, followed by Gene Ontology enrichment. Clinical validation included metabolomic profiling of 75 breast cancer patients and 20 controls. Results MR analysis identified 11 metabolites or metabolite ratios causally associated with cancer risk. Moreover, 48 proteins were demonstrated to be involved in the regulation of these metabolites, which are predominantly enriched in 5 significant metabolic pathways in cancers. Clinically, elevated lignoceroylcarnitine (C24) reduced breast cancer risk, while high glucose-to-mannose and alanine-to-asparagine ratios increased risk. Conclusions Our study revealed a causal effects of metabolites and its related proteins/pathways on various types of cancers.